SCREENING FOR ANTIMICROBIAL ACTIVITY OF SOME MEDICINAL PLANTS IN SAUDI ARABIA - Aly, M. M.; Bafeel, S. O. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Our study aimed to evaluate antimicrobial activities of some medicinal plants against some pathogenic yeasts and fungi. The antimicrobial activities of water and organic crude extracts of 6 medicinal plants used In traditional Saudi Arabia medicine was tested against to and pathogenic yeasts and fungi including strains that were highly resistant to amphotericin B and ketoconazole. Two species of yeasts: Candida albicans and C. tropicals and five species of pathogenic fungi: Aspergillus flavus, Alterneria solani, Fusarium oxisporium, Trichphyton rubrum, T. mentagrophyte and Microsporum nanum were used. Of the 6 plants tested, 5 showed antifungal activities against one or more spe-cies of fungi and 4 showed excellent activity against Candida albicans and C. tropicals. The most active antimicrobial plants were the ethanolic extract of Azadirachta indica(neem), Zingiber officinale (ginger) Eucalyptus globules and Lawsonia inermis with minimal inhibitory concentration (MIC) values ranged from 100 -250 Î¼g/ml. Rosmarinus officinalis and Lepidium sativum have moderate antifungal activates with MIC of 400 Î¼g/ml. No toxicity was recorded up to 300 Î¼g/ml. Moderate toxicity was recorded at 500 Î¼g/ml for A. indica and at 600 Î¼g/ml for E. globules. No antitumor activities were recorded using the Biochemical induction assay (BIA) and Escherichia coli as a test organism.